NILAI-NILAI PENDIDIKAN AGAMA ISLAM YANG TERKANDUNG DALAM TRADISI KHANDURI JRAT DI DESA RAYEUK NALEUNG KEC. TANAH LUAS - Sulaiman, Sulaiman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
Custom is a habit that has been a daily by a community for generations without any element of coercion from any party or factor. Most customs in society are influenced by belief in ancestors. One of the customs that has developed in Acehnese society, especially in the Tanah Luas District, North Aceh Regency, namely in Rayeuk Naleung village is khanduri jrat. The khanduri jrat tradition is similar to the usual grave pilgrimage procession. The tradition is carried out together with the extended family of the deceased at a public cemetery. The research method used in this research is the form of field research. Data collection techniques are by means of interviews, documentation and observation. The data analysis technique is by reducing the data, presenting the data and then take the conclusions from the data. The research results show that the implementation of khanduri jrat does not conflict with the teachings of the Islamic religion. Because the khanduri jrat tradition contains Islamic educational values, including the values ​​of aqidah, morals and worship. This is illustrated by the khanduri jrat procession from start to finish, which begins with work together, praying together, serving food and donating a little wealth.